Muhammad Iqbal's Thoughts: A Critical Analysis of the Reconstruction of Islamic Thought and Its Relevance to the Present - Muhammad Rasyid Ridho (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2025)
This article critically examines Muhammad Iqbal’s thought on the reconstruction of Islamic thought and its relevance to contemporary challenges. As a philosopher and reformer, Iqbal rejects stagnation and advocates for the revitalization of ijtihad and the integration of reason and revelation in understanding Islam. Using a qualitative and literature-based approach, this research analyzes Iqbal’s concept of khudi (selfhood) as the core of his intellectual reconstruction, aiming to develop creative, adaptive, and socially responsible Muslim individuals. The findings indicate that Iqbal’s ideas are highly relevant for addressing issues such as identity crises, spiritual poverty, and the challenges of globalization, particularly in the fields of education, theology, and character formation. Iqbal asserts the necessity of education that integrates spiritual values with modern rationality to produce a well-rounded individual (insan kamil) capable of competing in a globalized world. However, the implementation of Iqbal’s thought still faces significant challenges, including resistance from traditionalists and the risk of misinterpreting khudi as mere individualism. This article highlights Iqbal’s vital contribution to constructing a dynamic, humanistic, and contextually relevant paradigm for Islamic scholarship and civilization. The results of this study are expected to provide a foundation for contemporary Islamic renewal strategies and serve as inspiration for academics, educators, and policymakers.